Outcomes in Combined Anterior and Posterior Fusion for 3- and 4-Level Degenerative Lumbar Disc Disease - Haskins, Scott M.; Moskowitz, Alan; Lammli, John J.; Kuris, Eren O.; Chong, Alexander C.M. (Kansas Journal of Medicine, 2016)
Introduction. This study reported the clinical and functionaloutcomes in a consecutive series of patients with3- or 4-level degenerative disc disease (DDD) betweenvertebral levels L2 to S1, who were treated with combinedanterior lumbar interbody fusion (ALIF) and posteriorspinal fusion at one-year and two-year follow-ups.Methods. A retrospective chart review was performed on allpatients who underwent long segment fusion for DDD by asingle surgeon between August 2002 and January 2012. Fiftyfivepatients were identified and 32 had complete charts for review(14 had one-year follow-up and 18 two-year follow-up).In addition to demographic data, disability (Oswestry DisabilityIndex, ODI), pain level (Visual Analog Scale, VAS), andflexion-extension range-of-motion were measured pre- andpost-operatively. Operative data also were collected, includingoperative time, blood loss, surgical implants used, surgicalapproach, operative levels treated, and complications.Results. Both VAS and ODI improved significantly postoperatively.The average VAS score improved from 6.5 ± 1.5(range: 4 - 9) to 4.4 ± 1.7 (range: 2 - 7) for one-year follow-up,and 7.0 ± 1.8 (range: 4 - 10) to 4.4 ± 2.6 (range: 1 - 9) for twoyearfollow-up. For one-year follow-up, the average ODI scoreimproved from 53 ± 19% (range: 18 - 70%) to 37 ± 17% (range:12 - 64%), and for two-year follow-up, the average improvedfrom 53 ± 18% (range: 18 - 80%) to 31 ± 24% (range: 2 - 92%).The level of improvement in pain and function was similar topreviously published data for 1- and 2-level fusions, but overallpain and function scores were worse in this study group.Conclusions. Arthrodesis for 3- and 4-level DDD is, on average,a successful surgery that shows clinically significantimprovements in function and pain similar to fusionfor 1- and 2-levels with low rates of re-operation. Patientswith involvement of 3- or 4-levels have higher disabilityand pain both pre- and post-operatively compared to shorterfusion level involvement. KS J Med 2016;9(3):50-53.